ANALISIS KEMAMPUAN DAN KINERJA KEUANGAN DAERAH DI KOTA BANJARMASIN - ANGGI PUTRA WIGUNA (PPJP Universitas Lambung Mangkurat, 2018)
This study aims to analyze the condition and financial performance in the city of Banjarmasin as well as some efforts what has been done by the Government of Banjarmasin City in order to improve the ability and financial performance of the region.Results from the study during the period 2011-2016. Annual growth rate of 21.34%, so far has been successful in the process of local government, it looks quite large contribution of Local Revenue to the APBD is 14.12%. The degree of Fiscal Decentralization Banjarmasin during the period 2011-2016 is high with an average of 14.12%, said the pattern of relationship with infective. Meanwhile, the financial performance of Kota Banjarmasin from the side of fiscal needs is seen to increase during the period 2011-2016 average Rp. 313.493.023.747 billion means Fiscal Capacity greater than Fiscal Requirement. The average capacity of tax capacity is Rp. 344.725.786.194 or more. The fiscal position of Banjarmasin City, from the dimension of UPAD shows strong.Keywords: Financial Capability,Regional Finance,Financial Performance.